Makna Kesejahteraan Anak dalam Perspektif Pengalaman Subjektif : Studi Kualitatif pada Konteks Keluarga Modern - Sindi Agustin; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Early childhood well-being is becoming increasingly relevant amidst changing dynamics of modern families. Although objective indicators such as education and health show improvement, these do not fully reflect children's subjective experiences in everyday life. This study aims to examine the meaning of child well-being from the perspective of subjective experiences in the context of modern families. The method used was a qualitative literature review of articles, books, and research reports from 2020–2025, analyzed using thematic analysis. The results indicate that child well-being is primarily defined through emotional experiences, such as feeling loved, cared for, and closeness to parents. Meanwhile, technology plays a dual role, either supporting or diminishing the quality of interactions, depending on parental support. These findings underscore the importance of subjective perspectives in understanding child well-being and the need for more responsive parenting